Three Echinostome Species from Wild Birds in the Republic of Korea - Choe, Seongjun (The Korean Society for Parasitology and Tropical Medicine, 2014)
Three echinostome species, i.e., Patagifer bilobus, Petasiger neocomense, and Saakotrema metatestis, are newly recorded in the trematode fauna of the Republic of Korea. They were recovered from 3 species of migratory birds (Platalea minor, Podiceps cristatus, and Egretta garzetta), which were donated by the Wildlife Center of Chungbuk (WCC) and the Conservation Genome Resource Bank for Korean Wildlife (CGRB). Only 1 P. bilobus specimen was recovered from the intestine of a black-faced spoonbill (P. minor), and characterized by the bilobed head crown with a deep dorsal incision and 54 collar spines. Twenty P. neocomense were recovered from the intestine of a great crested grebe (P. cristatus), and they had a well-developed head crown with 19 spines and 2 testes obliquely located at the posterior middle of the body. Total 70 S. metatestis were collected from the bursa of Fabricius of 1 little egret (E. garzetta). It is characterized by stout tegumental spines covered in the entire leaf-shaped body, posterior extension of the uterus, presence of the uroproct and a well-developed head crown with 12 pairs of collar spines on each side. By the present study, these 3 echinostome species are newly added to the trematode fauna in Korea.